Optimalisasi Rantai Pasokan di UKM: Strategi Peningkatan Efisiensi dan Daya Saing - Permana, Indra Surya Permana; Qadaar, Amiruddin Qadaar (Jurnal Bisnis dan Kewirausahaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy, but there is room for improvement with regard to their supply chain management. This study aims to analyze the strategy for optimizing the MSME supply chain through a SWOT approach. The results of the analysis suggest that MSMEs may be able to enhance their operational efficiency and competitiveness by considering various strategies, including the utilization of digital technology, the expansion of human resource capacity, the strengthening of local supplier networks, and the promotion of product innovation and diversification. It is suggested that by implementing these strategies, MSMEs may have the opportunity to reduce operational costs, improve service quality, and expand markets. This research underscores the potential value of collaboration between MSMEs, the government, and the private sector in fostering a more efficient and sustainable supply chain ecosystem.